2017
DOI: 10.1038/s41598-017-08301-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate inhibits H2O2-induced apoptosis in Mouse Vascular Smooth Muscle Cells via 67kD Laminin Receptor

Abstract: Epigallocatechin-3-gallate (EGCG) is one of the major polyphenolic compounds present in green tea extracts and has been used as a potential drug for the treatment of numerous diseases. The present study aimed to elucidate the role and mechanism of EGCG in protecting against H2O2-induced apoptosis in mouse vascular smooth muscle cells (VSMCs). VSMCs were pretreated with various concentrations of EGCG for 2 hours prior to treatment with H2O2. Treatment with H2O2 significantly decreased the cell viability and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The non-integrin cell surface receptor, 67-kDa laminin receptor (67LR) is highly expressed on the surfaces of various tumour cells and is widely recognized as a molecular marker of metastatic aggressiveness 20,21 . Moreover, 67LR is a membrane receptor of EGCG 22 , and the binding of EGCG to the 67LR protein reportedly mediates many of EGCG's beneficial activities, such as its anti-proliferative and apoptosis-inducing effects on multiple tumour cells 23 , antioxidant effects 24,25 , and anti-inflammatory activities 26,27 .…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ The non-integrin cell surface receptor, 67-kDa laminin receptor (67LR) is highly expressed on the surfaces of various tumour cells and is widely recognized as a molecular marker of metastatic aggressiveness 20,21 . Moreover, 67LR is a membrane receptor of EGCG 22 , and the binding of EGCG to the 67LR protein reportedly mediates many of EGCG's beneficial activities, such as its anti-proliferative and apoptosis-inducing effects on multiple tumour cells 23 , antioxidant effects 24,25 , and anti-inflammatory activities 26,27 .…”
mentioning
confidence: 99%
“…5 e and f). EGCG has previously been reported to have a modulatory effect on the expression of apoptosis-related genes; mouse vascular smooth muscle cells cultured in a conditioned environment with H 2 O 2 showed significantly reduced expression of the pro-apoptotic genes caspase-3,8,9 and BAX and a significant increase in the expression of the anti-apoptotic gene BCL-2 after pre-treatment with EGCG [46] . Our results confirmed that the EGCG coating on the surface of PCL film was biologically active and influenced anti-oxidative signaling processes within hADSCs cultured on EGCG-coated film.…”
Section: Anti-apoptotic and Anti-oxidative Activities Of Egcg-coated Pcl Film Against H 2 Omentioning
confidence: 94%
“…Increasing evidence had suggested the contribution of the vascular smooth muscle cells (VSMCs) apoptosis to the pathogenesis of cardiovascular diseases, including hypertension, atherosclerosis, and even myocardial infarction (Kumar et al, 2014;Mill et al, 2014). Therefore, inhibiting VSMCs apoptosis could be a potential preventive strategy in slowing down the development of cardiovascular disease, especially for atherosclerosis (Yan et al, 2017). As oxidative stress is considered one of the most important pro-apoptotic stimuli leading to VSMCs apoptosis in atherosclerotic plaques (Korshunov and Berk, 2008), an effective antioxidant is imperatively needed to attenuate the oxidative stress-induced VSMCs apoptosis.…”
Section: Introductionmentioning
confidence: 99%